Atmospheric nitrogen deposition impacts on the structure and function of forest mycorrhizal communities: A review - Lilleskov, Erik A.; Kuyper, Thomas W.; Bidartondo, Martin I.; Hobbie, Erik A. (Environmental pollution (1987), 2019)
Humans have dramatically increased atmospheric nitrogen (N) deposition globally. At the coarsest resolution, N deposition is correlated with shifts from ectomycorrhizal (EcM) to arbuscular mycorrhizal (AM) tree dominance. At finer resolution, ectomycorrhizal fungal (EcMF) and arbuscular mycorrhizal fungal (AMF) communities respond strongly to long-term N deposition with the disappearance of key taxa. Conifer-associated EcMF are more sensitive than other EcMF, with current estimates of critical loads at 5–6 kg ha−1 yr−1 for the former and 10–20 kg ha−1 yr−1 for the latter. Where loads are exceeded, strong plant-soil and microbe-soil feedbacks may slow recovery rates after abatement of N deposition. Critical loads for AMF and tropical EcMF require additional study. In general, the responses of EcMF to N deposition are better understood than those of AMF because of methodological tractability. Functional consequences of EcMF community change are linked to decreases by fungi with medium-distance exploration strategies, hydrophobic walls, proteolytic capacity, and perhaps peroxidases for acquiring N from soil organic matter. These functional losses may contribute to declines in forest floor decomposition under N deposition. For AMF, limited capacity to directly access complexed organic N may reduce functional consequences, but research is needed to test this hypothesis. Mycorrhizal biomass often declines with N deposition, but the relative contributions of alternate mechanisms for this decline (lower C supply, higher C cost, physiological stress by N) have not been quantified. Furthermore, fungal biomass and functional responses to N inputs probably depend on ecosystem P status, yet how N deposition-induced P limitation interacts with belowground C flux and mycorrhizal community structure and function is still unclear. Current ‘omic analyses indicate potential functional differences among fungal lineages and should be integrated with studies of physiology, host nutrition, growth and health, fungal and plant community structure, and ecosystem processes. [Display omitted] •Mycorrhizal fungal communities change in composition in response to N deposition.•Critical loads for ectomycorrhizal fungi are lower for conifer than deciduous forests.•Community shifts likely respond to and cause changes in C, N, and P cycling.•Phylogenomic methods need integration with physiological and ecosystem studies.•Tropical and arbuscular mycorrhizal communities are poorly understood. Forest mycorrhizal fungal community composition responds strongly to N deposition across broad ranges of spatial, temporal and phylogenetic scales, with functional consequences—including altered tree nutrition and C, N, and P cycling—that are substantial but only partially understood.